Poblaciones de microartrópodos en diferentes suelos de Costa Rica - Serafino, Adolfo; Merino, Julio Fraile (Revista de Biología Tropical, 1978)
Density, vertical distribution and aggregation degree of soil microarthropod communities were studied between July and August of 1977 in the soils of three different plots, a forest and a pasture in Costa Rica. Data show the almost constant dominance of some groups of microarthropods (Isotomidae among the Collembola, Cryptostigmata among the Acarina and Symphila). There is a gradual decrease of density with depth, though not for all the groups, and a general tendency to an aggregate distribution. The hierarchical arder of densities of total microarthropod communities in the five localities was the following: maize, coffee, forest, manihot, and pasture.